2004
DOI: 10.1215/s1152851703000498
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 trial of irinotecan plus BCNU in patients with progressive or recurrent malignant glioma

Abstract: Irinotecan is a topoisomerase I inhibitor previously shown to be active in the treatment of malignant glioma. We now report the results of a phase 1 trial of irinotecan plus BCNU, or 1,3-bis(2-chloroethyl)-1-nitrosourea, for patients with recurrent or progressive MG. Irinotecan dose escalation occurred independently within 2 strata: patients receiving enzyme-inducing antiepileptic drugs (EIAEDs) and patients not receiving EIAEDs. BCNU was administered at a dose of 100 mg/m2 over 1 h every 6 weeks on the same d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…Antiemetic therapy with ondansetron and dexamethasone was given before each weekly dose of CPT‐11. Atropine (1 mg intravenously) was administered for acute cholinergic symptoms and loperamide was prescribed for late diarrhea as previously described 40. Hematopoietic growth factors and blood products were administered as indicated for Grade 4 hematologic toxicity.…”
Section: Methodsmentioning
confidence: 99%
“…Antiemetic therapy with ondansetron and dexamethasone was given before each weekly dose of CPT‐11. Atropine (1 mg intravenously) was administered for acute cholinergic symptoms and loperamide was prescribed for late diarrhea as previously described 40. Hematopoietic growth factors and blood products were administered as indicated for Grade 4 hematologic toxicity.…”
Section: Methodsmentioning
confidence: 99%
“…Irinotecan was administered weekly for 4 weeks at doses previously determined to be optimal for combination with BCNU and further stratified by EIAED status-225 mg/m 2 for those receiving and 125 mg/m 2 for those not receiving EIAEDs. 60 The phase II trial of 76 patients treated with this combination (37 newly diagnosed; 39 recurrent disease) showed the following results: five newly diagnosed patients (14%) achieved a radiographic response, including one complete response and four partial responses (95% CI, 5%-29%); five with recurrent disease (13%) demonstrated a response, including one complete response (95% CI, 4%-27%); and stable disease was demonstrated in more than 40%. 59 The median time to progression was 11.3 weeks for the recurrent GBM population and 16.9 weeks for patients with recurrent AA and anaplastic oligodendroglioma (AO).…”
Section: With Carmustinementioning
confidence: 99%
“…The usage of BCNU and irinotecan in combination has been described in the medical literature. The regimen seems to be active in patients with recurrent GBM and also appears to be non-crossresistant [2,15]. Recently a Phase II clinical trial involving BCNU and irinotecan showed that the activity of BCNU plus CPT-11 appears comparable to that of CPT-11 alone, and may be more toxic [17].…”
Section: Discussionmentioning
confidence: 99%